Multivalent conjugates of basic fibroblast growth factor enhance in vitro proliferation and migration of endothelial cells. (29th March 2018) - Zbinden, Aline; Browne, Shane; Altiok, Eda I.; Svedlund, Felicia L.; Jackson, Wesley M.; Healy, Kevin E.
Abstract : Multivalent growth factor conjugates hold great promise for regenerative therapies. Abstract : Growth factors hold great promise for regenerative therapies. However, their clinical use has been halted by poor efficacy and rapid clearance from tissue, necessitating the delivery of extremely high doses to achieve clinical effectiveness which has raised safety concerns. Thus, strategies to either enhance growth factor activity at low doses or to increase their residence time within target tissues are necessary for clinical success. In this study, we generated multivalent conjugates (MVCs) of basic fibroblast growth factor (bFGF), a key growth factor involved in angiogenesis and wound healing, to hyaluronic acid (HyA) polymer chains. Multivalent bFGF conjugates (mvbFGF) were fabricated with minimal non-specific interaction observed between bFGF and the HyA chain. The hydrodynamic radii of mvbFGF ranged from ∼50 to ∼75 nm for conjugation ratios of bFGF to HyA chains at low (10 : 1) and high (30 : 1) feed ratios, respectively. The mvbFGF demonstrated enhanced bioactivity compared to unconjugated bFGF in assays of cell proliferation and migration, processes critical to angiogenesis and tissue regeneration. The 30 : 1 mvbFGF outperformed the 10 : 1 conjugate, which could be due to either FGF receptor clustering or interference with receptor mediated internalization and signal deactivation. This study simultaneously investigated the role of both protein to polymer ratio and multivalent conjugate size on their bioactivity, and determined that increasing the protein-to-polymer ratio and conjugate size resulted in greater cell bioactivity.